FORESTFIRE AND ITS MANAGEMENT IN DISTRICT BANDIPORA JAMMU AND KASHMIR - Mohmad Yaseen Najar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
This paper presents the extent and magnitude of forest fires and adaptation responses to deepen our understanding of the dynamics of forest fires in District Bandipora. I used a narrative scooping review approach to narrate the present state of forest fires and resilient adaptation responses to guide the development of climate resilient adaptation pathways in the future. Forest fire presents significant threat to ecological integrity, human wellbeing, and global effort to fight climate change. Fire incidences are highest during and post dry winter months which quickly declines at the onset of monsoon. Adaptation and responding to ever growing size and frequency of forest fires are limited by lack of awareness, training on fire management, firefighting infrastructure, technology, and adequate policy and financial support. In addition, there is acute lack of scientific studies to understand forest fire dynamics in District Bandipora. Based on the forest fire literature we argue that policy makers and communities must quickly adopt policy strategies that support smart responses to forest fire management including allocating adequate funds to support capacity building and research.Such decision must be based on research into potentials for climate resilient pathways for adaptation response.